Malay language and the language of development: the roles of print media / Mohamad Razif Ibrahim and Siti Nur Farrah Faadiah Ab Ghani - Ibrahim, Mohamad Razif; Ab Ghani, Siti Nur Farrah Faadiah (2015)
The emergence of new media has posed serious threats towards the existence of print media. This is evident as challenges arise in maintaining the popularity of conventional media such as printed newspaper. Younger generation prefers online news as a quick and easy access to happenings although its use of language is questionable. Malaysian newspapers, however, are still showing its relevance among readers as a force of empowering the national language. Thus, this paper investigates, analyses and further explains the interrelationships between the roles of print media, such as newspapers, in promoting and strengthening Malay language in conjunction with the process of preserving Malay identity. The scope of this paper is print media available in Malaysia. This paper will contain ideas and recommendations on how the mentioned print media can help in contributing to the enhanced used of Malay language for preserving our Malay identity.